Altered Functional Connectivity of the Basal Nucleus of Meynert in Subjective Cognitive Impairment, Early Mild Cognitive Impairment, and Late Mild Cognitive Impairment - Xu, Wenwen; Rao, Jiang; Song, Yu; Chen, Shanshan; Xue, Chen; Hu, Guanjie; Lin, Xingjian; Chen, Jiu (Frontiers in Aging Neuroscience, 2021)
Background: The spectrum of early alzheimer's disease (AD) is thought to include subjective cognitive impairment, early mild cognitive impairment (eMCI), and late mild cognitive impairment (lMCI). The purpose of this study was to determine abnormal patterns of BNM-functional connectivity (BNM-FC) in the preclinical AD spectrum (SCD, eMCI, and lMCI) and further explore the relationships between these alterations and neuropsychological measures. Methods：Resting-state functional magnetic resonance imaging (rs-fMRI) was used to investigate the FC based on a seed mask (BNM mask) in 28 healthy controls (HC), 30 SCD, 24 eMCI, and 25 lMCI patients. Receiver operating characteristic (ROC) curve of abnormal BNM-FC was used to specifically determine the classification ability to differentiate the early AD disease spectrum relative to HC (SCD & HC, eMCI & HC, lMCI & HC) and pairs of groups in the AD disease spectrum (eMCI & SCD, lMCI & SCD, eMCI & lMCI). Results：Compared to the HC, the SCD patients showed increased FC in the bilateral SMA and decreased FC in the bilateral cerebellum and middle frontal gyrus (MFG), the eMCI patients showed significantly decreased FC in the bilateral precuneus and the lMCI individuals showed decreased FC in the right lingual gyrus. Compared to the SCD group, the eMCI group showed decreased FC in the right superior frontal gyrus (SFG), while the lMCI group showed decreased FC in the left middle temporal gyrus (MTG). Compared to the eMCI group, lMCI group showed decreased FC in the right hippocampus. Interestingly, the abnormal FC was associated with certain cognitive domains cognitive functions including episodic memory, executive function, information processing speed, and visuospatial function in the disease groups. Conclusions：The abnormal BNM-FC patterns can characterize early disease spectrum of AD (SCD, eMCI, and lMCI) and are closely related to the cognitive domains. These new and reliable findings will provide a new perspective in identifying the early disease spectrum of AD and further strengthen the role of cholinergic theory in AD.